The Displacement Analysis Investigation for Variable Gradient Parameters Functionally Graded Materials Based on Strip Element Method. (24th May 2018) - Tian, J. H.; Ma, L. L.
Abstract : This paper adopted the strip element method to research the displacement response of functionally graded material structure with variable gradient parameters under mechanical loading. Based on the dynamic equilibrium equation of the system, strip element method theory was established through the principle of virtual work to get the control equations of functionally graded materials plane problem, using the modal superposition method to complete the solution of the equation and obtain the displacement distribution of the FGM plates with variable gradient parameters. The accuracy of the calculation method was verified by comparison with the result of finite element method. The results show that the displacement response of the strip element method is consistent with the finite element method. With the increase of the gradient coefficient, the ceramic content is increased and the material stiffness is also increased; then the displacement response caused by external loading is decreased. With the increase of the gradient coefficient, the influence of the gradient coefficient on the displacement response is decreased gradually.